2014
DOI: 10.1097/pcc.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated Heparin Activity Measured by Anti-Factor Xa Levels Is Associated With the Need for Extracorporeal Membrane Oxygenation Circuit/Membrane Oxygenator Change

Abstract: Rationale Traditional measures of anticoagulation, including activated clotting time (ACT), have been poorly correlated with circuit thrombosis in pediatric patients supported with extracorporeal membrane oxygenation (ECMO). Objective Investigate whether anti-Factor Xa levels are associated with the need for change of circuit/membrane oxygenator secondary to thrombus formation in pediatric patients. Design and Settings Retrospective single institution study. Patients and Methods Retrospective record revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 22 publications
2
64
1
1
Order By: Relevance
“…In hospitalized patients who required heparin for cardiovascular indications, aPTT and antiXa levels were discordant the majority of the time; high aPTT/in-range antiXa discordance predicted major bleeding and mortality (4). In pediatric ECMO patients, lower antiXa levels (but not ACT or aPTT levels) were associated with circuit thrombosis, although hemostatic changes that occur during early life makes it difficult to generalize this observation to adults (5). …”
Section: Dear Editormentioning
confidence: 99%
“…In hospitalized patients who required heparin for cardiovascular indications, aPTT and antiXa levels were discordant the majority of the time; high aPTT/in-range antiXa discordance predicted major bleeding and mortality (4). In pediatric ECMO patients, lower antiXa levels (but not ACT or aPTT levels) were associated with circuit thrombosis, although hemostatic changes that occur during early life makes it difficult to generalize this observation to adults (5). …”
Section: Dear Editormentioning
confidence: 99%
“…Anticoagulation monitoring studies have demonstrated a lack of correlation between the anti-Xa test and ACT or aPTT in all patient populations. 55,56 Irby and colleagues 57 demonstrated an association between subtherapeutic anti-Xa levels and an increased need for oxygenator exchanges, suggesting potential benefi ts of the anti-Xa test. The relationship between ACT and aPTT has also shown inconsistencies; better correlations have been found between heparin doses and aPTT than between heparin doses and ACT.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Heparin is difficult to monitor in these patients for a variety of reasons including low antithrombin levels, low coagulation factor levels, lupus inhibitors, hemolysis, and icterus. The activated clotting time has been used for ECLS unfractionated heparin monitoring, but has been called into question due to its lack of correlation with heparin dose, anti‐Xa heparin activity, partial thromboplastin time (PTT), bleeding, or circuit thrombosis . The PTT has also been used to monitor unfractionated heparin during ECLS, but it has been reported to show high levels of discordance with anti‐Xa heparin activity assays, due to low or high coagulation factor levels, lupus inhibitors, contact factor deficiencies, and other causes …”
Section: Introductionmentioning
confidence: 99%
“…The activated clotting time has been used for ECLS unfractionated heparin monitoring, but has been called into question due to its lack of correlation with heparin dose, anti-Xa heparin activity, partial thromboplastin time (PTT), bleeding, or circuit thrombosis. [1][2][3][4][5][6] The PTT has also been used to monitor unfractionated heparin during ECLS, but it | 881 KHAN ANd CHANdLER has been reported to show high levels of discordance with anti-Xa heparin activity assays, due to low or high coagulation factor levels, lupus inhibitors, contact factor deficiencies, and other causes. [7][8][9][10] Anti-Xa heparin activity assays are becoming a standard approach for monitoring heparin during ECLS.…”
Section: Introductionmentioning
confidence: 99%